2012
DOI: 10.3130/aija.77.157
|View full text |Cite
|
Sign up to set email alerts
|

A Proposed Rational Behind the Ancient Khmer's Dimensional Planning at the Beng Mealea

Abstract: Based on the results of previous studies on planning methods and procedures of various Khmer monuments, we attempted to analyze the case of Beng Mealea. The construction measure is considered to be 411mm, however, dimensional inconsistencies are revealed in details of some parts. The objective of this paper is to examine the planning methods and process of Beng Mealea temple by a restorative approach.Judging from the result of analysis, the planning of Beng Mealea was started with double-enclosure temple layou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Drawing on these knowledges, Mizoguchi et al conducted a series of analyses on the classic Khmer architecture in eastern Thailand, Angkor monuments, Koh Ker, and the isolated temples of Beng Mealea and Preah Vihear. The current results by his team indicated that the true length of a hasta was 412 mm (Mizoguchi et al, 2007(Mizoguchi et al, , 2009(Mizoguchi et al, , 2010a(Mizoguchi et al, , 2010b(Mizoguchi et al, , 2012. Based on the analysis of each shrine in Sambor Prei Kuk, the construction unit for individual shrines were estimated to be around 407.5 mm (Narui et al, 2019).…”
Section: Analyzing the Planning Technique Behind Prasat Sambormentioning
confidence: 83%
“…Drawing on these knowledges, Mizoguchi et al conducted a series of analyses on the classic Khmer architecture in eastern Thailand, Angkor monuments, Koh Ker, and the isolated temples of Beng Mealea and Preah Vihear. The current results by his team indicated that the true length of a hasta was 412 mm (Mizoguchi et al, 2007(Mizoguchi et al, , 2009(Mizoguchi et al, , 2010a(Mizoguchi et al, , 2010b(Mizoguchi et al, , 2012. Based on the analysis of each shrine in Sambor Prei Kuk, the construction unit for individual shrines were estimated to be around 407.5 mm (Narui et al, 2019).…”
Section: Analyzing the Planning Technique Behind Prasat Sambormentioning
confidence: 83%